PEG-b-AGE polymer coated magnetic nanoparticle probes with facile functionalization and anti-fouling properties for reducing non-specific uptake and improving biomarker targeting1. Issue 17 (7th May 2015) - Li, Yuancheng; Lin, Run; Wang, Liya; Huang, Jing; Wu, Hui; Cheng, Guojun; Zhou, Zhengyang; MacDonald, Tobey; Yang, Lily; Mao, Hui
<x xml:space="preserve">Abstract</x> PEG-b-AGE copolymer has been developed for IONP coating to provide anti-biofouling property and improve biomarker targeting.